Measurements of Dielectric and Magnetic materials at Microwave and Millimeter Waves - QUAN, WEI. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Electrical Engineering.; Advisor: Mohammed Afsar.; Committee: Usman Khan, Nian Sun, and Austin Napier.; Keyword: Electrical engineering.